Time span from onset of oral cancer symptoms to treatment: a hospital based cross sectional study in South India - Somanna, Shivaraj Nallur; Sastry, Nandakumar Bidare; Cheluvarayaswamy, Ramesh; Sabitha, K. S.; Srinivasa, Murthy Nandagudi; Malila, Nea (International Journal Of Community Medicine And Public Health, 2018)
Background: Oral cancer is one of the major health problems in India. Patient delay in seeking medical help usually contributes to late stage at diagnosis, high mortality and low survival. Our study aims to find the time span from first onset of oral cancer symptoms to cancer specific primary treatment. Methods: A cross-sectional study was carried out from October 2015-September 2016 in one of the tertiary care cancer center in Bangalore. Histopathologically confirmed 212 incident oral cancer patients were interviewed using a pre-tested semi structured questionnaire. Results: The median time span between onset of symptoms and seeking medical care was 60 [IQR 30, 104] days, the median time between seeking medical care and diagnosis was 30 [IQR 15, 90] days, and the median time between diagnosis and initiation of treatment was 20 [IQR 12, 33] days. Conclusions: There is considerable delay in seeking cancer specific primary treatment among oral cancer patients. Efforts should be undertaken to increase awareness in the population and all stakeholders regarding symptoms and improve early diagnostics and access to care.